2023
DOI: 10.1177/11786302231157507
|View full text |Cite
|
Sign up to set email alerts
|

Honoring Indigenous Sacred Places and Spirit in Environmental Health

Abstract: Indigenous Peoples and their deep knowledges offer a fundamentally important way of seeing the world and the environment. Through relationships to distinct ancestral homelands, Indigenous Peoples have developed unique ways of surviving, adapting, connecting, and relating to their respective environments. Indigenous Sacred Places themselves are connections to ancestors, to all beings on the planet, and to different planes of existence. Sacred Places serve an important environmental role in many Indigenous Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Appendix 1 outlines the results of the MMAT quality appraisal of the individual studies. One study was identified as a mixed method (Nawrath et al, 2022 ), nine as qualitative studies (Bellehumeur et al, 2022 ; Lestar & Böhm, 2020 ; Cloud & Redvers, 2023 ; Denis et al, 2022 ; Hategan, 2021 ; Keaulana et al, 2021 ; Skoko et al, 2021 ; Nalau et al, 2018 ; Oberholzer-Dent et al, 2023 ), and four as quantitative studies (Kras & Keenan, 2020 ; Oliveira et al, 2022 ; Vitorino et al, 2018 ; Walls et al, 2022 ). All included studies addressed both screening questions, stated the research aims, and justified the findings to answer the research questions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations

Ecospirituality and Health: A Systematic Review

de Diego‑Cordero,
Martínez-Herrera,
Coheña-Jiménez
et al. 2024
J Relig Health
“…Appendix 1 outlines the results of the MMAT quality appraisal of the individual studies. One study was identified as a mixed method (Nawrath et al, 2022 ), nine as qualitative studies (Bellehumeur et al, 2022 ; Lestar & Böhm, 2020 ; Cloud & Redvers, 2023 ; Denis et al, 2022 ; Hategan, 2021 ; Keaulana et al, 2021 ; Skoko et al, 2021 ; Nalau et al, 2018 ; Oberholzer-Dent et al, 2023 ), and four as quantitative studies (Kras & Keenan, 2020 ; Oliveira et al, 2022 ; Vitorino et al, 2018 ; Walls et al, 2022 ). All included studies addressed both screening questions, stated the research aims, and justified the findings to answer the research questions.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship with nature must include an exchange in which every time the environment gives us something, we give it back in another way, thus establishing a spiritual connection. The belief of many indigenous people is that everything in the universe is related and that is why all “energy” comes and goes forming a circle (Cloud & Redvers, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations

Ecospirituality and Health: A Systematic Review

de Diego‑Cordero,
Martínez-Herrera,
Coheña-Jiménez
et al. 2024
J Relig Health
“…The review showed that climate change enhanced multiple processes of vulnerability specific to Indigenous Peoples, as well as providing more indirect and intangible mental health evidence [124]. Indigenous perspectives of the world are holistic in nature and that the whole is considered to be alive with Spirit that requires respect and reverence, because all life has a place in the Sacred Hoop of Life, which many call the Medicine Wheel [125]. The Medicine Wheel is a teaching tool used by many North American Indigenous cultures in Knowledge Translation/transmission [126].…”
Section: Discussionmentioning
confidence: 99%